La politique de revitalisation de la langue basque dans la communauté autonome basque - Eguzki Urteaga (Lengas)
This article focuses on the policy of revitalization of the Basque language developed and then implemented by the Basque Government, in collaboration with public institutions and private entities, in the Basque Autonomous Community located in the Iberian Peninsula. Based on the sociolinguistic situation of the Basque language and the sociodemographic factors having an impact on its evolution, and taking into account the legal framework in force and the commitments made by the public authorities at the autonomous, national and european levels, it analyses the linguistics policy in favour of the knowledge and practice of Basque, paying particular attention to its objectives and strategic axes, its actions and its budget, its governance and its monitoring. It appears that this language policy is relatively effective, having enabled the training of 300,000 additional Basque speakers in the space of three decades.